Diagnostic value of BIRADS method using sonography in evaluating the level of malignancy of breast masses compared with biopsy - Donya Farrokh; Seyyed Ali Alamdaran; Ali Feizy; Hamed Soleimany (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Ultrasound is a valuable diagnostic imaging modality in the clinical evaluation of breast masses. BIRADS (Breast Imaging Reporting and Data System) classification in ultrasound is an important and reliable method for assessment and estimation of the risk of malignancy in breast lesions. This study was performed with aim to evaluate the accuracy of the results of BIRADS classification (Grade 3 and 4) using sonography in evaluating the level of malignancy of breast masses and comparing it with pathology results. Methods: This study was performed on 139 patients referred to Imam Reza hospital, Omid Oncology hospital and some private clinics in Mashhad and evaluated the patients with palpable breast mass who were ultrasound candidates for further examination of the nature of mass in 2014-2016. Axilla breast ultrasound was performed by two radiology professors. Based on the classification of the American Radiology Society and BIRADS system, various degrees of breast masses malignancy were identified, and then the patients were referred for biopsy. The pathologic results were compared with ultrasound reports, and consistency of the results and accuracy of ultrasound were examined with statistical tests. Data were analyzed by SPSS software (version 16). Results: Out of 37 biopsies of lesions with BIRADS-3 in ultrasound, two (5.4%) of the lesions resulted in malignant pathology. Out of 102 biopsies of lesions with BIRADS-4 in ultrasound, 65 (64%) resulted in benign pathology which indicates no consistency of pathology results with sonography in these cases. The sensitivity of the BIRADS-3 system for diagnosis of benign breast masses was 94% and its specificity was 64%. The sensitivity of the BIRADS-4 system for diagnosis of malignant breast cancers was 75% and its specificity was 79%. Conclusion: There was consistency between the results obtained from the classification by the BIRADS method and pathology; so regarding the relatively high accuracy of this method, radiologic-pathologic consistency can be used to determine how to follow the patients and choose the appropriate treatment method.